Mulheres no contexto da rua: a questão do gênero, uso de drogas e a violência - Machado, Mayk Diego Gomes da Glória (2016)
In this study we propose to understand the meanings attributed by female homeless drug users and on their experiences in this context. Supported theoretically on Feminist Psychology, along with the Gender Studies and Interdisciplinary Studies in Health, the research was presented in three chapters: Homeless People: reflections on abjection, women and drugs; The Feminist Movement and Gender Concept: implications for Psychology and Mental Health; Construction of a methodological route for data analysis: a critical feminist perspective. It was used in this study a qualitative methodology, epistemological setting that aligns the social constructionism and Women's Studies and Gender. As a tool, we chose to perform interviews. Dialogical maps were developed in order to analyze the interviews into four categories: homeless; drug use behavior, violence suffered; being a woman on the street. It is possible to point out, as a result, the gender perspective proves to be very useful to understand the experiences of homeless women, highlighting the experiences of rape, psychological and physical violence in the course of their lives. The use of drugs emerges to alleviate inequalities in gender relations. These data can contribute for planning and intervention in public policies for homeless. It is necessary more research for a critical analysis of the effectiveness of homeless’s public policies, taking women into consideration.